Delayed Giant Splenic Artery Aneurysm Following Splenic Infarction in a Patient with Infective Endocarditis - Yangzong Z; Gui X; Wen Q; Qian H; Shi L; Liu X (International Medical Case Reports Journal)
Zhaxi Yangzong,1,* Xiying Gui,1,* Qingping Wen,1,* Hua Qian,1 Li Shi,1 Xinchao Liu1,2 1Department of Infectious Disease, Tibet Autonomous Region People’s Hospital, Lhasa, People’s Republic of China; 2Department of Infectious Disease, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences, Peking Union Medical College, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Shi, Department of Infectious Disease, Tibet Autonomous Region People’s Hospital, No. 18, Linkuo North Road, Chengguan District, Lhasa, Tibet, People’s Republic of China, Email shili6869@163.com Xinchao Liu, Department of Infectious Disease, Peking Union Medical College Hospital, No. 1 Shuaifuyuan Wangfujing Dongcheng District, Beijing, 100730, People’s Republic of China, Email xcliu2009@126.comAbstract: Infective endocarditis is a severe infectious disease that, in addition to cardiac complications such as heart failure and arrhythmias caused by valve damage, may also lead to extracardiac complications such as septic embolization, metastatic abscesses, and mycotic aneurysms. Here, we report a rare case of splenic infarction resulting from infective endocarditis, subsequently leading to the development of a splenic artery aneurysm three weeks post-surgery confirmed both by CTA and DSA. Following arterial embolization of the aneurysm, the patient eventually recovered completely.Keywords: infective endocarditis, splenic infarction, pseudoaneurysm